A climatology of the California Current System from a network of underwater gliders. (May 2017) - Rudnick, Daniel L.; Zaba, Katherine D.; Todd, Robert E.; Davis, Russ E.
Abstract: Autonomous underwater gliders offer the possibility of sustained observation of the coastal ocean. Since 2006 Spray underwater gliders in the California Underwater Glider Network (CUGN) have surveyed along California Cooperative Oceanic Fisheries Investigations (CalCOFI) lines 66.7, 80.0, and 90.0, constituting the world's longest sustained glider network, to our knowledge. In this network, gliders dive between the surface and 500 m, completing a cycle in 3 h and covering 3 km in that time. Sections extend 350–500 km offshore and take 2–3 weeks to occupy. Measured variables include pressure, temperature, salinity, and depth-average velocity. The CUGN has amassed over 10, 000 glider-days, covering over 210, 000 km with over 95, 000 dives. These data are used to produce a climatology whose products are for each variable a mean field, an annual cycle, and the anomaly from the annual cycle. The analysis includes a weighted least-squares fit to derive the mean and annual cycle, and an objective map to produce the anomaly. The final results are variables on rectangular grids in depth, distance offshore, and time. The mean fields are finely resolved sections across the main flows in the California Current System, including the poleward California Undercurrent and the equatorward California Current. The annual cycle shows a phase change from the surface to the thermocline, reflecting the effects of air/sea fluxes at the surface and upwelling in the thermocline. The interannual anomalies are examined with an emphasis on climate events of the last ten years including the 2009–2010 El Niño, the 2010–2011 La Niña, the warm anomaly of 2014–2015, and the 2015–2016 El Niño.